Study on hot cracking susceptibility of alloy 617M and an analysis on parameters used for its evaluation. (August 2021) - M., Divya; Dey, H.C.; Das, C.R.; M., Vasudevan; Albert, Shaju K.
Abstract: Hot cracking study on nickel base superalloy, alloy 617M, a candidate material for Advanced Ultra Supercritical (AUSC) power plant applications, was carried out. The susceptibility of this alloy to solidification cracking was evaluated using varestraint (variable restraint) test set up and parameters like Brittleness Temperature Range (BTR) and Critical Strain rate per Temperature drop (CST) were estimated from the results. The BTR and CST for alloy 617M indicate higher susceptibility to solidification cracking than stabilized and un-stabilized austenitic stainless steels. However, mock-up welding of 400 mm diameter alloy 617M hollow forgings with weld thickness of 95 mm and alloy 617M boiler tubes of 12 wall thickness made from this alloy did not reveal any significant cracking in the welds (except some isolated micro fissures) and hence, a detailed analysis of the results from varestraint tests was taken up. The study revealed the dual hot cracking behaviour of alloy 617M and the reasons behind such observation is elucidated. The microstructural characterisation of the hot crack tested specimens of alloy 617M revealed eutectics of austenite + carbides rich in Mo and Cr in the backfilled regions of the hot cracks in the fusion zone. The formation of significant fraction of eutectic phases along the interdendritic regions at the end of solidification is the primary reason for the high BTR exhibited by alloy 617M. Further, backfilling of the solidification cracks by this eutectic liquid is enabled under low augmented strain and the same is insufficient to aid backfilling in cracks at high restraints. The mechanism mentioned above was found to be the underlying reason for the dual behaviour revealed by alloy 617M. Hence, it was deduced that BTR and CST determined at saturated strain cannot be effectively used to predict the actual hot cracking behaviour of alloy 617M. A refined criterion-BTR at threshold strain is proposed to be an appropriate solidification cracking susceptibility index for this alloy.